The Efficacy of STEM-Integrated Teaching Materials in Improving High School Students' Critical Thinking Skills - Ahmad Saputra; Insih Wilujeng; Antuni Wiyarsi; Sigit Priatmoko (Pendidikan Kimia, 2026)
Education is a key pillar of a nation's progress. Results from the Program for International Student Assessment (PISA) 2022 indicate that Indonesian students' performance in reading, mathematics, and science remains below international averages, reflecting persistent challenges in higher-order thinking and problem-solving skills. This study aimed to develop STEM- based teaching materials integrated with 21st-century learning to enhance students' critical thinking skills. The research employed a Research and Development (R&D) approach using the 4D model (define, design, develop, disseminate). Participants included material and media experts, chemistry teachers, and 36 Grade XI students. Critical thinking skills were measured using pretest–posttest assessments aligned with Ennis' indicators, expert validation sheets, and student response questionnaires. The results showed that expert feasibility ratings reached 98.05% (highly feasible), user responses were 88.79%, and readability was 87.83%. The effectiveness of the materials was supported by a high N-Gain score of 0.73, indicating substantial improvement in students' critical thinking skills. Overall, the developed teaching materials were feasible, well-received, and effective in improving students' critical thinking skills. These findings imply that systematically integrating STEM principles with 21st-century learning skills can serve as an effective instructional strategy to strengthen higher-order thinking in chemistry education. Future research is recommended to conduct large-scale experimental studies across diverse school contexts and to explore digital integration to enhance scalability and long-term impact.